Nilai Perusahaan Sebagai Variabel Moderating: Studi Empiris Profitabilitas Perusahaan Sub Sektor Logam Dan Sejenisnya Di BEI Tahun 2016-2018 Dalam Kaitannya Dengan Good Corporate Governance (GCG) Dan Pengungkapan Corporate Social Responsibility (CSR) - Suyatno, Suyatno (Journal of Entrepreneurship, Management and Industry (JEMI), 2021)
The objective of this study is to examine the influence of Good Corporate Governance (GCG) and disclosure of Corporate Social Responsibility (CSR) with regard to the company’s capability of making profits with corporate value as the moderating variable in manufacturers engaging in the basic industrial sector listed on the Indonesia Stock Exchange. This study involved 6 manufacturing companies engaging in the basic industrial sector listed with the Indonesia Stock Exchange during the 2016-2018 period as the uses purposive samples. This study uses multiple linear regression analysis with SPSS (Statistical Product and Service Solution) application tools as the analytical method used. It found out that Good Corporate Governance has no correlation with profitability while Corporate Social Responsibility affects profitability. On the other hand, Corporate value is unable to moderate Good Corporate Governance towards profitability and Company value is unable to moderate Corporate Social Responsibility with regard to profitability as well.